IMPLEMENTASI PROGRAM SERTIFIKASI GURU DALAM UPAYA PENINGKATAN KINERJA PENDIDIK - Apep Munajat; Heru Sujiarto; Hanafiah Hanafiah; Ahmad Khori (Balai Diklat Keagamaan Bandung, 2022)
This study aims to describe and analyze the implementation of certification and post-certification teacher performance by using Terry's management theory (planning, organizing, mobilizing, and supervising, teacher certification, and teacher performance). The method used is descriptive qualitative method. Data collection techniques include in-depth interviews, observation, and documentation. To test the validity of the data by triangulation. The locus of research was conducted in Cianjur Regency. The data sources consist of the Ministry of Religion of Cianjur Regency, Supervisors, Heads of Madrasas, teachers, documents to certification related, and teacher performance. The implication is that the constraint factors are too strong compared to supporting factors and contribute to the sluggish and challenging attainment of certification requirements.Keywords: implementation, teacher certification; and performance